The X chromosome is necessary for ovule production in Silene latifolia. - Paris Veltsos; Lynda F Delph (PLoS ONE, 2019)
Sex chromosomes stop recombining and accumulate differences over time. In particular, genes on the chromosome restricted to the heterogametic sex degenerate and become non-functional. Here, we investigated whether or not the degeneration of a plant Y chromosome was sufficient to cause ovules containing a Y to fail to develop, thereby eliminating the possibility of YY individuals. We used two genotypic assays to determine the genotype-XX, XY, or YY-of offspring from a single fruit of an otherwise normal male XY plant of Silene latifolia. The fruit contained fewer ovules than normal pistillate flowers, produced an equal offspring sex ratio, and generated no YY offspring. The results indicate that ovaries must contain an X chromosome to develop properly. While haploid selection has slowed down Y-chromosome degeneration in S. latifolia, we find that it has progressed sufficiently to prevent the proper development of ovules, and hence prevent the presence of YY individuals.